2006
DOI: 10.1029/2005jc003033
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the sea ice simulation in a new coupled atmosphere‐ocean climate model (HadGEM1)

Abstract: [1] A rapid increase in the variety, quality, and quantity of observations in polar regions is leading to a significant improvement in the understanding of sea ice dynamic and thermodynamic processes and their representation in global climate models. We assess the simulation of sea ice in the new Hadley Centre Global Environmental Model (HadGEM1) against the latest available observations. The HadGEM1 sea ice component uses elastic-viscous-plastic dynamics, multiple ice thickness categories, and zero-layer ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
57
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(60 citation statements)
references
References 48 publications
3
57
0
Order By: Relevance
“…Investigation of the seasonal biases in West Antarctic climate of some of the bestperforming and worst-performing models was consistent with this. However, the realistic simulation of the seasonal cycle of sea ice presents a number of problems for climate models besides the correct representation of the atmosphere component, namely the correct representation of ocean currents and the complicated thermodynamical and dynamical processes within the ice pack (e.g., McLaren et al 2006). Turner et al (2013a) showed that the majority of the CMIP5 models have a seasonal cycle of sea ice extent that differs markedly from the observations, whereas Zunz et al (2012) showed that the CMIP5 multimodel mean underestimates (overestimates) the SIE in the ABS and Ross Sea sectors over the period from 1979 to 2005 in February (September), which are the months where the sea ice cover reaches its minimum (maximum).…”
Section: Discussionmentioning
confidence: 99%
“…Investigation of the seasonal biases in West Antarctic climate of some of the bestperforming and worst-performing models was consistent with this. However, the realistic simulation of the seasonal cycle of sea ice presents a number of problems for climate models besides the correct representation of the atmosphere component, namely the correct representation of ocean currents and the complicated thermodynamical and dynamical processes within the ice pack (e.g., McLaren et al 2006). Turner et al (2013a) showed that the majority of the CMIP5 models have a seasonal cycle of sea ice extent that differs markedly from the observations, whereas Zunz et al (2012) showed that the CMIP5 multimodel mean underestimates (overestimates) the SIE in the ABS and Ross Sea sectors over the period from 1979 to 2005 in February (September), which are the months where the sea ice cover reaches its minimum (maximum).…”
Section: Discussionmentioning
confidence: 99%
“…As melting 1 m of sea ice will reduce pCO 2 levels by 14 µatm in a 20 m water column according to the calculations above, ∼4 m of sea ice would need to melt locally to explain the low pCO 2 concentrations in the water column. In polynya areas the sea ice production is usually much greater than indicated by the annual sea ice thickness due to the continued production of ice (McLaren, 2006). The local ice production at POLY I is thus likely responsible for much more larger ice growth than the April-May ice thickness of 1.4-1.6 m usually observed at ICE I .…”
Section: Role Of Ikaite In Seawater Co 2 System and Gas Exchangementioning
confidence: 96%
“…The atmosphere has 38 vertical levels with a model top at 39 km. Detailed description of the model formulation can be found in Shaffrey et al (2009, Martin et al (2006), McLaren et al (2006) and references therein.…”
Section: Higem Climate Modelmentioning
confidence: 99%